Protective effects of melatonin against spinal cord injury induced oxidative damage in rat kidney: A morphological and biochemical study - YEGEN, BERRAK; AKAKIN, DİLEK; ŞENER, GÖKSEL; ÖZKAN YENAL, NAZİYE; ÖZDEMİR KUMRAL, ZARİFE NİGAR (ELSEVIER GMBH, 2013)
Spinal cord injury (SCI) induced oxidative stress affects multiple organ systems including the kidney. We studied the possible protective effects of melatonin on SCI-induced oxidative damage in renal tissues of rats. Wistar albino rats (n =24) were exposed to SCI and divided into vehicle- or melatonin-treated SCI groups. Melatonin was administred intraperitoneally at a dose of 10 mg/kg for seven days. Renal tissues were investigated by light and electron microscopy. Furthermore, tissue malondialdehyde (MDA) and glutathione (GSH) levels and myeloperoxidase (MPO) and superoxide dismutase (SOD) activities were also determined. In the vehicle-treated SCI group, the renal histology was disturbed compared to controls, whereas the melatonin-treated SCI group showed significantly reduced degeneration of renal tissue as seen by both light and electron microscopy. MDA levels, MPO and SOD activities were increased and GSH levels were decreased in the vehicle-treated SCI group compared to controls. On the other hand, decreased MDA levels and MPO activities and increased GSH levels were observed in the melatonin-treated SCI group compared to vehicle-treated SCI group. These results showed that experimentally induced SCI caused oxidative stress in the rat kidney, whereas melatonin treatment reduced oxidative stress, suggesting that it may be used as a complementary therapy of renal problems occurring following SCI. (C) 2013 Elsevier GmbH. All rights reserved.
Keywords: Oxidative stress; Spinal cord injury; Melatonin; Kidney; Ultrastructure; SYSTEMIC INFLAMMATORY RESPONSE; URINARY-BLADDER; MYELOPEROXIDASE; NEPHROTOXICITY; CONTUSION; DEFICITS; STRESS; TRAUMA